Anti-quorum sensing potential of selenium nanoparticles against LasI/R, RhlI/R, and PQS/MvfR in Pseudomonas aeruginosa: a molecular docking approach - Kanak, Kanak Raj; Dass, Regina Sharmila; Pan, Archana (Frontiers in Molecular Biosciences, 2023)
Pseudomonas aeruginosa is an infectious pathogen which is able to cause primary and secondary contagions in the blood, lungs, and another body parts of immunosuppressed individuals, as well as community-acquired diseases such as folliculitis, osteomyelitis, pneumonia, and others. This opportunistic bacterium displays drug resistance and regulates its pathogenicity via the Quorum Sensing (QS) mechanism, which includes the LasI/R, RhlI/R, and PQS/MvfR systems. Targeting the QS systems might be an excellent way to treat P. aeruginosa infections. Although a wide array of antibiotics namely newer Penicillins, Cephalosporins and combination drugs are being used, the utility of Selenium nanoparticles (SeNPs) to cure P. aeruginosa infections are extremely scarce as their mechanistic interactions are weakly understood which results to carry out this study. The present study demonstrates a computational approach of binding interaction pattern between SeNPs and the QS signaling proteins in P. aeruginosa, utilizing multiple bioinformatics approaches. The computational investigation revealed that SeNPs were acutely 'locked' into the active region of the relevant proteins. The PatchDock-based molecular docking analysis has evidently indicated the strong and significant interaction between SeNPs and catalytic cleft of LasI synthase (Phe105-Se = 2.7 Å and Thr121-Se = 3.8 Å), RhlI synthase (Leu102-Se = 3.7 Å and Val138 = 3.2 Å), transcriptional receptor protein LasR (Lys42-Se = 3.9 Å, Arg122-Se = 3.2 Å and Glu124-Se = 3.9 Å), RhlR (Tyr43-Se = 2.9 Å, Tyr45-Se = 3.4 Å and His61-Se = 3.5 Å) and MvfR (Leu208-Se = 3.2 Å and Arg209-Se = 4.0 Å). The production of Acyl Homoserine Lactones (AHLs) was inhibited by the use of SeNPs, thereby preventing QS as well. Obstructing the binding affinity of transcriptional regulatory proteins may cause the suppression of LasR, RhlR, and MvfR systems to become inactive, thereby blocking the activation of QS-regulated virulence factors along with their associated gene expression. Our findings clearly show that SeNPs have anti-QS properties against the established QS systems of P. aeruginosa, which strongly advocating that SeNPs might be a potent solution to tackle drug resistance and a viable alternative to conventional antibiotics along with helpful in therapeutic development to cure of P. aeruginosa infections.